New Channels and Ways of Delivering Public Services in Pre-school Education Institutions - Liukinevičienė, Laima; Paulauskienė, Vaida (Socialiniai tyrimai, 2019)
A smart society starts from pre-school age. Aiming to implement the National Education Strategy for 2013–2022, the considerable attention is paid to the involvement of children into pre-school education, where their individual skills would be more actively disclosed. It is therefore essential to develop alternatives within education system, which would be accessible, attractive and valuable to those groups of society that are currently not sufficiently enough involved into education. Considering that the economic well-being of the Republic of Lithuania is growing and the employment is increasing, the requirements for the quality and availability of public services are increasing in the society, it is worth to be mentioned that Lithuanian society also expects more accessibility and quality of services in pre-school education institutions. The aim of the research is to reveal the possibilities of new ways and channels of delivering public service in pre-school education institutions. Having conducted the content analysis of scientific literature and synthesis of ideas substantiated with scientific analysis as well as having conducted qualitative research in pre-school education institutions of Mažeikiai County Municipality, the research is based on the case of Mažeikiai county. The selection of the research object – public services in pre-school education institutions and their delivery ways and channels – is based on the aim of education policy to increase the accessibility, repeatability, individualization of services for early education as well as the increasing interest in modern ways of service delivery in Lithuania, by combining direct and indirect service delivery channels. In the second decade of the 21st century, scientists’ attention paid to the personalization and particularity of the service is increasing, as the user’s needs and the supplier’s possibilities are growing. Innovative technical channels and a whole set of instruments are increasingly being used to personalize services (A. Patapas, V. Vilutytė-Žilienė, 2013, pp. 312–325; A. Jonas, 2016, p. 206). Services are often available through several different distribution channels, which, according to L. Bagdonienė et al. (2004), are understood as the chains of entities (individuals and organizations) involved in the delivery of services and performing specific functions. There are two types of service delivery channels – direct and indirect (through intermediaries) – distinguished by authors, and on the basis of the latest scientific literature, we have included one more channel, when both channels are combined. Direct service delivery may be provided at the provider’s institution or in the consumer’s location, or some services may be provided at either location. Meanwhile, the indirect service channel can take many forms, whose structures are rapidly changing and they are increasingly complex, with active use of e-services, m-services and smart services. In Lithuania,10-15 years ago, direct education services included all educational services (education and care, educational assistance, parent education, etc.) and most of social services (nutrition, health care, social and psychological assistance, ensuring of physical, social and emotional security, family support, etc.). Today, we are talking about combining these channels and the increasing involvement of stakeholders and social partners into service delivery. In this way, modern service delivery channels could be: 1) alternative to the traditional channel (direct service delivery at the provider’s institution or at the recipient’s home) when digital technologies are used, according to the provider’s choice or the recipient’s choice, 2) chains and networks created by inter-institutional co-operation and partnership, when educational and social services are delivered both directly (recreational services for children and family, temporary education and care, child care centres, babysitting services, social and psychological assistance in pre-school education institution or at home, etc.) and indirectly (e-communication with parents, informing about health, social support from local authorities, issues on children’s rights, supply of extracurricular activities, involvement in local community activities, etc.), usually by coordinating delivery channels. The analysis of the material collected during the semi-structured interview (six heads of pre-school education institutions in Mažeikiai county and one specialist from education department who works with kindergartens were interviewed) allowed to distinguish the following particularities and perspectives of the delivery of modern pre-school education services: Delayed political decisions are among the external factors that hinder the increased use of modern services and delivery channels. The process is promoted by opportunities created by information technology and migration, as emigrants returning to Lithuania want new, more diverse services for their children. Of the internal factors that influence the development of modern services, the competence of the staff of pre-school education institution is the most significant. At present, it is of paramount importance in educational services, without avoiding to introduce alternative educational programs. There is active learning to ensure the social and emotional safety of children, but there is the lack of deeper understanding and readiness to provide family support services and work with at-risk families. Inter-institutional cooperation is important in service supply chain. It has increased in providing educational, physical, emotional security services for a child; there is the lack of active social interaction with other institutions in providing family support and social security services. Through the combination of direct and indirect service delivery channels, the use of digital technologies is important, and informants see their potential in increasing access to services, increasing diversity of services, reducing the disparity in service availability between urban and rural areas, and creating new quality of education. In Lithuania, it has not been prepared so far for the model of pre-school education at home and family support, and during the transitional period there would be an approval for mobile kindergarten groups. Nanny service, as an alternative service to early childhood education, is provided only in exceptional situations, and it would be viable in the cities and its funding should be complex; the pedagogical and value competence of a nanny is important as well.